(untitled) (Advancements in Homeopathic Research, 2024)
Homoeopathy, a complementary and alternative medicine (CAM) system, was founded by Dr Samuel Hahnemann in 1796. Its fundamental principle is "like cures like," which implies that any substance capable of developing specific symptoms in a healthy person can treat those similar symptoms in a diseased person. India is the world’s largest user and propagator of homoeopathy.